Liberating and Enlightening Education on Qur’anic Perspective - Ahmad Zain Sarnoto; Sri Tuti Rahmawati; Lamya Hayatina (Islamic Research, 2022)
This research is to reveal that education is not only dealing with issues of intelligence and thinking, but it is also fully responsible for the development of students' character. Due to the said reason, it is important to explore such research considering that the mental situation of this nation is clearly correlated with the spirit of national education which has been value free. Our educational philosophy is indeed intellectual, but our learning strategy is no longer concerned with the mental, moral, and developmental aspects of enlightening thinking skills. The national education curriculum and methodology are designed only to fill the mind with a series of knowledge and do not provide enough opportunity for the growth of an enlightened human being. Al-Qur'an for Muslims is not a mere a religious scripture, but it is also indeed to be an enlightening guide to find some basic principles of education which can then inspire in developing a qualified education. This study uses the Qur'anic literature method as well as a descriptive and qualitative research with a library research approach by analysing Qur’anic verses. This article analyzes the signs of al-Qur'an as the basic framework for building a liberating and enlightening education.